2016
DOI: 10.4103/0974-8237.193257
|View full text |Cite
|
Sign up to set email alerts
|

Spinal intradural hydatid cyst causing arachnoiditis: A rare etiology of cauda equina syndrome

Abstract: This study aims to focus on a rare presentation of spinal hydatid cyst as cauda equine syndrome and misdiagnosed as intradural extramedullary (IDEM) benign lesion on magnetic resonance imaging. In this article, we report a case of spinal hydatid cyst masquerading as IDEM tumor, and intraoperatively, we accidently find clumped granuloma with severe arachnoiditis and hydatid cyst in lumber region, which was present as bilateral S1 radiculopathy with cauda equina syndrome. An 11-year-old boy who presented with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[ 7 ] The diagnostic feature is the presence of a markedly hypointense cyst wall on T1- and T2-weighted images. [ 6 ] However, rare location with unusual finding of involvement of intervertebral disc and absence of characteristic features make the diagnosis difficult as seen in the described case. The differentials on radiology include tuberculosis, aneurysmal bone cyst, synovial cyst, traumatic pseudomeningocele, arachnoid cyst, and hemangiomas.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[ 7 ] The diagnostic feature is the presence of a markedly hypointense cyst wall on T1- and T2-weighted images. [ 6 ] However, rare location with unusual finding of involvement of intervertebral disc and absence of characteristic features make the diagnosis difficult as seen in the described case. The differentials on radiology include tuberculosis, aneurysmal bone cyst, synovial cyst, traumatic pseudomeningocele, arachnoid cyst, and hemangiomas.…”
Section: Discussionmentioning
confidence: 93%
“…[ 5 ] They can present either with compressive myelopathy or radiculopathy. [ 6 ] MRI is the preferred diagnostic modality when there is a suspicion of hydatid disease. [ 7 ] The diagnostic feature is the presence of a markedly hypointense cyst wall on T1- and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engamba et al reported a case in which a patient presented with CES which resulted from the rupture of an underlying aortic aneurysm [7]. In a report by Singh et al, an 11-year-old boy was determined to have CES, which resulted from an underlying spinal hydatid cyst, which was initially thought to be an intradural extramedullary benign lesion [8]. Metastatic cancer has also been reported to cause CES.…”
Section: Discussionmentioning
confidence: 99%
“…Other presenting symptoms include radiculopathy, myelopathy and pathological fractures. 25 , 36 , 42 57 However, the patient may be asymptomatic in the early stages of the disease. 42 In a study of 36 patients with spinal echinococcosis, 10 patients presented with backache, and 17 patients experienced variable degree; four patients experienced complete paraplegia, another four patients experienced urinary retention, and one patient experienced quadriplegia.…”
Section: Clinical Presentationmentioning
confidence: 99%